Pelo viés da teatralização: A pedra do reino por Antunes Filho - Lucimara de Andrade (2017)
The present research investigates Antunes Filho's creative process, in particular the play A Pedra do Reino, theater adaptation of Ariano Suassunas novels A Pedra do Reino and O Rei Degolado, approaching reflections about issues related to directors theatrical operation context. In this perspective, we seek to delineate the procedures and means which constitute the staging of the fiction narratives, developed by Antunes throughout his trajectory, his interlocution with Ariano, the authorship concept problematization, the dialogical references, the processes of scenic composition and Antuness scenic poetry, his preparation methods for actors, his notions of theaterizing, prêt-à-porter, manifestation, fonemol, among others. In theaterizing of A Pedra do Reino (2006) we highlight the bare stage, the actors' blocks, the multireferential aspect of the montage, the authorial co-creation, the choreographic dynamics, the musical language, the citations and erasures, besides other conventions and scenic innovations of Antunes.